2019
DOI: 10.18203/2320-1770.ijrcog20191939
|View full text |Cite
|
Sign up to set email alerts
|

Cholestasis of pregnancy: a prospective analysis from a South Andaman teaching hospital

Abstract: Background: Intrahepatic cholestasis of pregnancy (IHCP) is one of the commonest pregnancy related liver disorder. Although the maternal course is usually benign, there is an increased risk of spontaneous preterm delivery, fetal compromise, meconium stained amniotic fluid and even intrauterine fetal demise. The objective of this study was to study the incidence of IHCP and its impact on maternal and perinatal outcome.Methods: A prospective study carried out in 68 number of IHCP cases. Diagnosis was done on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Mean gestational age was 36.11 ± 2.75 weeks in the pregnancy which is complicated by IHC within the study group. Mean age of 37 and 38 weeks was reported by Pegu et al [1] and Arthuis et al [14] in their similar study.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Mean gestational age was 36.11 ± 2.75 weeks in the pregnancy which is complicated by IHC within the study group. Mean age of 37 and 38 weeks was reported by Pegu et al [1] and Arthuis et al [14] in their similar study.…”
Section: Discussionsupporting
confidence: 81%
“…Pathogenesis of IHC is thought to be multifactorial, mostly depending on genetic configuration, geographical area, environmental changes, and ethnicity. In the present study, there [1] Rook et al, [3] and Pokhrel et al [4] who were found that 2.73%, 1.9%, and 1.15%, respectively, in their study population.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations